Murine monoclonal antibodies against murine uPA receptor produced in gene-deficient mice: Inhibitory effects on receptormediated uPA activity in vitro and in vivo - Pass, Jesper; Jögi, Annika; Lund, Ida K.; Rønø, Birgitte; Rasch, Morten G.; Gårdsvoll, Henrik; Lund, Leif R.; Ploug, Michael; Rømer, John; Danø, Keld; Høyer-Hansen, Gunilla (Thrombosis and Haemostasis, 2007)
Binding of urokinase plasminogen activator (uPA) to its cellular receptor, uPAR, potentiates plasminogen activation and localizes it to the cell surface. Focal plasminogen activation is involved in both normal and pathological tissue remodeling processes including cancer invasion. The interaction between uPA and uPAR therefore represents a potential target for anti-invasive cancer therapy. Inhibitors of the human uPA-uPAR interaction have no effect in the murine system. To enable in-vivo studies in murine cancer models we have now generated murine monoclonal antibodies (mAbs) against murine uPAR (muPAR) by immunizing uPAR-deficient mice with recombinant muPAR and screened for antibodies, which inhibit the muPA-muPAR interaction. Two of the twelve mAbs obtained, mR1 and mR2, interfered with the interaction between muPAR and the amino-terminal fragment of muPA (mATF) when analyzed by surface plasmon resonance. The epitope for mR1 is located on domain I of muPAR, while that of mR2 is on domains (II-III). In cell binding experiments using radiolabelled mATF, the maximal inhibition obtained with mR1 was 85% while that obtained with mR2 was 50%. The IC50 value for mR1 was 0.67 nM compared to 0.14 nM for mATF. In an assay based on modified anthrax toxins, requiring cell-bound muPA activity for its cytotoxity, a ~50% rescue of the cells could be obtained by addition of mR1. Importantly, in-vivo efficacy of mR1 was demonstrated by the ability of mR1 to rescue mice treated with a lethal dose of uPA-activatable anthrax toxins.
Keywords: Plasminogen activation; uPAR knock-out mice; mouse antimouse mAbs; inhibitors of uPA-uPAR interaction; anthrax toxin assay